2021
DOI: 10.1161/atvbaha.120.315612
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Autofluorescence in Atherosclerosis Associates With Ceroid and Is Generated by Oxidized Lipid-Induced Oxidative Stress

Abstract: Objective: Near-infrared autofluorescence (NIRAF) of atherosclerosis associates with intraplaque hemorrhage and is detectable in living patients with coronary artery disease. However, further mechanisms underlying NIRAF generation have not been fully characterized. Here, we investigated the role of lipids and oxidative stress in NIRAF generation in atherosclerosis and in vitro in human macrophages. Approach and Results: In N=15 human caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Lipid metabolic disorders often produce ROS, which leads to oxidative damage. Studies have also shown that ROS can regulate lipid metabolism (Albaghdadi et al, 2021;Chen et al, 2021;Li et al, 2021). Aberrant metabolism of TG is the main cause of fatty liver, and the most intuitive manifestation in steatosis is the accumulation of TG (Yu et al, 2021;Zhang Z. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolic disorders often produce ROS, which leads to oxidative damage. Studies have also shown that ROS can regulate lipid metabolism (Albaghdadi et al, 2021;Chen et al, 2021;Li et al, 2021). Aberrant metabolism of TG is the main cause of fatty liver, and the most intuitive manifestation in steatosis is the accumulation of TG (Yu et al, 2021;Zhang Z. et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared autofluorescence (NIRAF) has been associated with lipids and intraplaque hemorrhage. Macrophages, which are a marker of a vulnerable plaque, phagocytose extravasated red blood cells, degrade heme to bilirubin, and are involved in the formation of insoluble lipids or ceroids 29,31 . Here we show that the aforementioned endogenous near-infrared biomarkers, especially in colocalization with macrophages, can be detected by PAI.…”
Section: Spatial Transcriptomic Sequencing and Proteomics Highlights ...mentioning
confidence: 99%
“…Recently, bilirubin and other heme degradation products and insoluble lipid in atherosclerotic plaques have been evaluated as to their autofluorescence properties in the near-infrared (680 nm) range 29 . The hemoglobin degradation products represent a pathological process indicative of intraplaque hemorrhage and therefore serve as an important biomarker for vulnerable plaque [29][30][31] . However, near-infrared autofluorescence (NIRAF) in the 650-700 nm range suffers from limited penetration depth and spatial resolution; and therefore, photoacoustic techniques are attractive 22,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Htun et al reported bilirubin (formed from biliverdin by biliverdin reductase) to be the likely source of NIRAF, based on the co-localization of bilirubin with IPH in plaque, and the positive association between plaque bilirubin concentrations and NIRAF in the TS mouse model of plaque instability [ 2 ]. In apparent contrast, Albaghdadi et al observed elevated NIRAF in the absence of co-localized IPH and bilirubin in human carotid endarterectomy specimens, and instead suggested an insoluble oxidized lipid or ceroid as a source of NIRAF [ 5 ]. Thus, the roles of IPH and bilirubin in the NIRAF of atherosclerotic plaque remain unclear; however, knowledge of the underlying molecular mechanism(s) is important to better understand the biological relevance and clinical significance of NIRAF-based imaging strategies.…”
Section: Introductionmentioning
confidence: 99%